Investigating Mitochondrial Choline Metabolism in Macrophages - Pember, Ciara (Université d'Ottawa / University of Ottawa, 2023)
The essential nutrient choline is known to serve as a precursor for phospholipids and the neurotransmitter acetylcholine, and to feed into methylation pathways. The role and fate of choline in immune cells, however, is not yet fully elucidated. To act as a methyl group donor, choline must first undergo oxidation in mitochondria, a process which has long been thought to occur exclusively in the liver and kidney. The recent identification of choline transporters on the mitochondrial membrane has highlighted the possibility of mitochondrial choline oxidation in other cell types. Here, I show that choline transporters are present on the mitochondrial membrane of primary and immortalized mouse macrophages. The interaction of CTL2 with mitochondria is further augmented following pro-inflammatory polarization with the bacterial endotoxin lipopolysaccharide. I show that mitochondrial choline uptake occurs in macrophages using radiolabelled choline assays; however, it remains unclear whether this process is conducted through the identified transporters. Preliminary data suggest that mitochondrial choline oxidation to betaine was increased in LPS-stimulated macrophages, revealing a potential additional input into one-carbon metabolism in polarized macrophages. This project broadens the existing paradigm that choline oxidation occurs strictly in hepatic and renal tissue and suggests that choline oxidation may be a regulated process in macrophage polarization.
Keywords: Macrophage; Choline; Inflammation; Oxidation; Lipopolysaccharide